THE IMPACT OF FINTECH COMPANIES ON THE TRADITIONAL BANKING SECTOR: COMPETITIVE INTERACTIONS AND OPPORTUNITIES FOR COOPERATION (European Journal of Economics, Finance and Business Development, 2024)
The rapid growth of fintech companies has significantly transformed the competitive dynamics within the financial sector. This study examines the impact of fintech activity on the performance of traditional banks, focusing on competitive interactions and potential opportunities for collaboration. Using a panel econometric analysis of data from 150 commercial banks across various countries from 2010 to 2022, we investigate how fintech innovation influences banks' return on assets (ROA). The results reveal that increased fintech activity exerts a statistically significant negative effect on the ROA of traditional banks, indicating heightened competitive pressure. However, this impact is moderated by bank-specific factors such as size and capital adequacy, as well as macroeconomic conditions. Larger banks and those with higher capital adequacy ratios are less adversely affected, suggesting that scale and financial stability provide resilience against fintech competition. The study also highlights that in economies with higher GDP growth, the negative influence of fintech on banks is diminished. These findings underscore the necessity for traditional banks to adapt by investing in technological innovations and exploring strategic partnerships with fintech firms. Such adaptations can mitigate competitive threats and harness potential synergies, contributing to sustained profitability and market position.